The Effectiveness Of The Project Based Learning Model In The Independent Learning Curriculum - Nur Halimatusyadiyah; Salsabella Wawa Anasya; Azan Pajri (UNIVERSITAS PGRI YOGYAKARTA, 2022)
This study aims to determine the effectiveness of the Project Based Learning learning model in the independent learning curriculum in schools. This research uses descriptive qualitative method through literature study. Data collection in this study was carried out by means of study and search from various relevant sources in the form of articles or results of previous research. The data are analyzed and studied in depth. There are two variables in this study, namely the Project-based learning (PJBL) learning model and the independent learning curriculum.